Congenital dislocation of pisiform bone: A case report and review of literature (Journal of Pakistan Orthopaedic Association, 2020)
Pisiform dislocation is very rare. Only few cases have been reported and all were post- traumatic. Due to its rarity, there is no optimum treatment. Literature suggest close reduction and open reduction or excision of pisiform with good results. We present a case of dislocated pisiform identified post traumatically in a 10-year-old female with ipsilateral greenstick radius and ulna fracture. She presented in emergency room(ER) after a simple fall over the outstretched hand. X-rays and CT scan confirmed the dislocated pisiform bone. The pisiform bone was surgically excised. The patient was given a below elbow back slab for 4 weeks. At 3 months, follow up she was completely pain free with full range of motion of wrist and no functional deficit. We suggest that excision of Pisiform bone after dislocation can be performed without the risk of any future consequences. Removal of bone does not interfere with normal wrist function.